How does a bout of repeated spiking affect shoulder muscle activity during a rapid arm raise task? A study of trained male volleyball players - White, W. (2022)
There is a high prevalence of overuse injuries in volleyball, which can result in participation time loss. The game of volleyball involves repetitive overhead movements such as serving and spiking. Overhead motions rely on effective movement of the scapula, produced by the shoulder muscles. Muscle fatigue may affect scapula thoracic (ST) muscle function, and in turn affect scapula kinematics. Overuse injuries, such as subacromial impingement syndrome (SIS), have been linked to dysfunctional scapula kinematics and ST muscle activity among overhead athletes. The causal nature of this link is unclear, that is, does injury lead to altered kinematics and muscle function, or vice versa? If injury arises due to dysfunctional scapula control, then states of fatigue could increase the risk of injury by causing changes in muscle function.